Lost in the sun - Graff, Lisa (Lisa Colleen), 1981- (Puffin Books, 2016)
As middle schooler Trent Zimmerman struggles to move past a traumatic event that took place several months earlier, he befriends class outcast Fallon Little, a girl with a scar across her face, who helps him understand that he can move on.